ON PROBLEM OF THE COMPOSITION OF BUKHARA MARKET AND VOLUME OF TRADE IN LATE MEDIEVAL PERIOD - Jakhongir Yunus ugli, Ergashev (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the analyses of information on the market relations in the Bukhara khanate during the medieval ages, as well as their organization and social groups that were actively involved in the process. Furthermore, goods that were sold in Bukharan markets and stores are discussed. The article explores the features of trade and economic relations in the regions during the late medieval period.